PEMBERDAYAAN MASYARAKAT DALAM UPAYA MENCEGAH STUNTING DENGAN “GUe CANTIG” PADA REMAJA PUTRI DI MTs GUPPI SUMURUP KECAMATAN BENDUNGAN KABUPATEN TRENGGALEK - Rahayu Niningasih; Elok Yulidaningsih; Awan Hariyanto (Politeknik Kesehatan Kemenkes malang, 2021)
MTs GUPPI Sumurup, Bendungan is one of private schools in the region of Bendungan Community Health Center, with the total number of 138 students, consisted of 66 male and 76 female students. Bendungan district is an upland area and its most residents are farmers for their living. Most of the students of MTs GUPPI are coming from the local area in Bendungan district. Based on the preliminary study in January 2019 conducted by the official staff of Bendungan Community Health Center, it was found that most of them have not been screened yet regarding Hemoglobin checking, so that there was no data dealing with the Anemia case. This Community Dedication Program aimed to elevate the knowledge of the students regarding the Anemia and to measure the level of Hemoglobin of MTs GUPPI students. The methods used in this program were counseling and education about Anemia as well as taking the level of students’ Hemoglobin. Before that, the students were prescribed Fe tablets and observed within 8 weeks. The result pointed out that there was significant improvement of students’ knowledge regarding Anemia and their level of Hemoglobin was in normal state